Comparative perspectives on criminal justice in China - McConville, Mike; Pils, Eva (Edward Elgar Publishing Ltd., 2013)
'This highly informative and engaging volume on the Chinese criminal justice system today provides a window into the vagaries of law and its operation in the People's Republic. McConville and Pils bring together an impressive array of scholars whose studies span the criminal process. From initial police investigation, through to prosecution and sentencing of defendants, we see how dominant values in the Chinese state and its structures of power make the practice of criminal justice today still intensely political.' - Susan Trevaskes, Griffith University, Australia. © The Editors and Contributors Severally 2013. All rights reserved.
CRIS-Team Scopus Importer:2023-03-21